PENINGKATAN KEMAMPUAN MENULIS PUISI DENGAN MENGGUNAKAN MEDIA POSTCARD - Ni Made Suardani (sarasvati, 2021)
This study aims to describe the improvement of the learning process, the attitudes of students, and the results of learning to write poetry with POSTCARD MEDIA for students of class VIII Α SMP Angkasa. This research is a Classroom Action Research (PTK) with research subjects consisting of 22 students. This action research was conducted in two cycles, each of which contained four components, namely planning, implementing, observing, and reflecting. Observation data were obtained through tests, observations, document analysis, interviews, and questionnaires. The data analysis technique used qualitative and quantitative descriptive analysis techniques through descriptive statistical techniques. The results showed that the application of postcard media could improve students' poetry writing skills and motivation in learning to write poetry. The improvement of students' poetry writing skills can be seen from the quality of the process, positive attitudes, and learning outcomes of students during the learning activities to write poetry. The process improvement and positive attitudes of students in participating in learning activities are indicated by the activeness, interest, motivation, enthusiasm and seriousness of students who have increased in each cycle.